PERANCANGAN GAME KUIS INTERAKTIF SEBAGAI MULTIMEDIA PEMBELAJARAN DRILL AND PRACTICE UNTUK MENINGKATKAN HASIL BELAJAR SISWA - Miftah Farid Adiwisastra (LPPM Universitas Bina Sarana Informatika, 2015)
Abstract - This study aims to build a model of multimedia learning such as drill and practice that improve for student learning outcomes. The method used is us in this research is a method of research and development (R & D). Its for test the performance of the media as well as determine the feasibility of this game was tested to the field. It is hoped this game could help improve student learning outcomes. This study also aims to determine the views and interests of students towards learning using multimedia learning model of drill and practice, and to see the validity or appropriateness interactive quiz game that has been built as well as to see the students' multimedia assessment have been developed. Questionnaires were used in this study include field survey questionnaire used is given to two junior high school students of Islamic Boarding School Darul Muta'allimin Tasikmalaya and student assessment questionnaire to the interactive quiz game. In this research showed that almost all of the students gave positive responses regarding the use of multimedia learning model such as drill and practice with an interactive quiz game, students give a very good assessment of the learning multimedia interactive quiz game with a percentage rating of 91, 979%, and get increased learning outcomes. Keywords : Multimedia Learning, Drill and practice, Interactive Quiz Game Abstrak - Penelitian ini bertujuan untuk membangun multimedia pembelajaran model drill and practice untuk meningkatkan hasil belajar siswa. Metode yang digunakan dalam penelitian ini adalah metode penelitian dan pengembangan atau Research and Development(R&D). Menguji kinerja media serta mengetahui tingkat kelayakan game ini diujikan ke lapangan. Diharapkan game ini mampu membantu meningkatkan hasil belajar siswa. Penelitian ini juga bertujuan untuk mengetahui pandangan dan ketertarikan siswa terhadap pembelajaran yang menggunakan multimedia pembelajaran model drill and practice dan untuk melihat validitas atau kelayakan game kuis interaktif yang telah dibangun serta untuk melihat penilaian siswa terhadap multimedia yang telah dikembangkan. Kuisioner yang digunakan dalam penelitian ini diantaranya adalah kuisioner survey lapangan yang diberikan kepada 2 siswa SMP IBS Darul Muta’allimin Tasikmalaya dan kuisioner penilaian siswa terhadap game kuis interaktif. Dari penelitian ini didapatkan hasil yaitu hampir seluruh siswa memberikan respon positif mengenai pembelajaran yang menggunakan multimedia pembelajaran model drill and practice dengan game kuis interaktif , siswa memberikan penilaian sangat baik terhadap multimedia pembelajaran game kuis interaktif dengan persentase penilaian sebesar 91.979%, dan mengalami peningkatan hasil belajar. Kata kunci : Multimedia Pembelajaran, Drill and practice, Game kuis interaktif